Analysis of human resource processes and their influence on bonuses and benefits - Madero Gómez, Sergio Manuel; Peña Rivera, Humberto (Cuadernos de Administración, 2012)
Today, companies are more competitive, transforming their processes daily to improve, particularly in the development of strategies to impact upon their goals, especially in human talent. This research seeks to know the relevance of the many practices of human resource management (pay policies, job descriptions, job evaluation, pay structure, communication, etc.) in payment of bonuses and incentives to workers; however, the perception exists of the person relating success, motivation or the importance of income through work compensation, for which we identified in a sample of 335 subjects that indeed a relationship does exist among these variables; this was carried out through a model of structural equations, based on the Partial Least Squares, which confirms the relevance of human resource practices in compensation management, revealing a correlation of r(335)=0.72, p<0.001 with the bonds and benefits received by the worker.